2020
DOI: 10.1016/s2468-1253(20)30300-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of irritable bowel syndrome-type symptoms in patients with inflammatory bowel disease in remission: a systematic review and meta-analysis

Abstract: This is a repository copy of Prevalence of irritable bowel syndrome-type symptoms in patients with inflammatory bowel disease in remission: a systematic review and metaanalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
138
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 68 publications
7
138
0
3
Order By: Relevance
“…Some data about the prevalence of this phenomenon have already been gathered. The most recent meta-analysis by Faibrass et al [79] revealed that 28.7% of patients in UC remission and 36.6% in CD remission reported IBS-like symptoms-substantially, this phenomenon was more common in those with CD than UC. Altogether, 35.2% (ranging from 11.2% to 63.6%) of patients diagnosed with IBD, in general, have symptoms similar to IBS without ongoing disease activity.…”
Section: Remission Of Ibd and Ibs-like Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some data about the prevalence of this phenomenon have already been gathered. The most recent meta-analysis by Faibrass et al [79] revealed that 28.7% of patients in UC remission and 36.6% in CD remission reported IBS-like symptoms-substantially, this phenomenon was more common in those with CD than UC. Altogether, 35.2% (ranging from 11.2% to 63.6%) of patients diagnosed with IBD, in general, have symptoms similar to IBS without ongoing disease activity.…”
Section: Remission Of Ibd and Ibs-like Symptomsmentioning
confidence: 99%
“…What is more, according to Simren et al [80], IBS-like symptoms appear to correspond rather with the duration of the disease than with patients' age, administered treatment, or extension of the disorder. However, they were more frequent in females, especially with high levels of anxiety and depression [1,2,79,81].…”
Section: Remission Of Ibd and Ibs-like Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are also aware of the importance of overlap between organic disease and functional symptoms, with a particular focus on inflammatory bowel disease. 4,5 Nevertheless, the population prevalence of these disorders is much lower than IBS, and our recent validation study of the Rome IV criteria for IBS demonstrated these criteria are more sensitive and specific than the previous iteration, Rome III. 6 Consequently, despite having no access to medical records, we believe that it is reasonable to assume the majority had IBS since our cohort met the Rome IV criteria for IBS.…”
mentioning
confidence: 98%
“…We are certainly not suggesting IBS is a diagnosis of exclusion. We are also aware of the importance of overlap between organic disease and functional symptoms, with a particular focus on inflammatory bowel disease 4,5 . Nevertheless, the population prevalence of these disorders is much lower than IBS, and our recent validation study of the Rome IV criteria for IBS demonstrated these criteria are more sensitive and specific than the previous iteration, Rome III 6 .…”
mentioning
confidence: 99%